Ribosomal DNA ITS1, 5.8S and ITS2 secondary structure, nuclear DNA content and phytochemical analyses reveal distinctive characteristics of four subclades of Protasparagus. Issue 1 (25th August 2016) - Saha, Partha Sarathi; Sengupta, Mainak; Jha, Sumita
Abstract: The use of ribosomal DNA (rDNA) internal transcribed spacer (ITS) primary sequence based phylogeny is a conventional practice to estimate the evolutionary interspecies relationship. However, analysis of the functional folding patterns and higher order secondary structures of ITS regions can provide additional important information regarding species relatedness and interspecies variations. In the present study, we provide the first detailed information on the rDNA ITS secondary structure diversity in the four subclades of the subgenus Protasparagus . Several angiospermic conserved motifs were identified in each of the ITS1, 5.8S and ITS2 secondary structures of the studied taxon. Topological comparison of the ITS1 secondary structures showed variations in the helix‐ IV regions. Moreover, presence of unique sequence motifs and differences in the internal loop structures were found to be subclade specific. The present study suggests that comprehensive analysis of the ITS1, 5.8S and ITS2 structural elements including helices, loops and bulges can be used as an important tool for species delimitation. The present study investigated the evolution of the secondary structure of ITS marker (its phylogenetic utility), genome size, base chromosome number and phytochemicals, and identified a putative polyploid event shared by a number of Protasparagus species. The phytochemical analysis of two important active compounds, i.e., shatavarin‐IV and sarsasapogenin, also reveals their presence in all the studied taxa constitutively even at the subclade level.